2011
DOI: 10.1080/10407790.2011.630956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turbulence Models and Near-Wall Modeling Approaches on Numerical Results in Impingement Heat Transfer

Abstract: In this study, turbulence models and near-wall modeling approaches were compared in impingement heat transfer. The Reynolds-averaged Navier-Stokes (RANS) turbulence models were compared using three near-wall modeling approaches. Moreover, the effect of near-wall modeling approaches on heat transfer was investigated and the predictions were compared with experiments. All computations were performed with the FLUENT code by considering two-dimensional, steady, and incompressible flow. Wall functions (WF) should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…Recently, Sagot et al [74] considered two k-ε and two k-ω models for non-swirling impinging jet heat transfer and found that SST k-ω agrees well with their experimental data, in agreement with [77]. Although the standard k-ε model has been found to be inaccurate in the past in predicting stagnation region heat transfer, interestingly, a recent work [72] reported significant improvement with standard k-ε models if combined with a two-layer model of enhanced wall treatment. In summary, even though very little work has been done on characterising the effects of different modelling approaches when applied to swirling impinging jets, the diversity of works already done on other flow configurations also makes it hard to anticipate the sensitivity of specific models when applied to turbulent impinging jets.…”
Section: Introductionsupporting
confidence: 60%
“…Recently, Sagot et al [74] considered two k-ε and two k-ω models for non-swirling impinging jet heat transfer and found that SST k-ω agrees well with their experimental data, in agreement with [77]. Although the standard k-ε model has been found to be inaccurate in the past in predicting stagnation region heat transfer, interestingly, a recent work [72] reported significant improvement with standard k-ε models if combined with a two-layer model of enhanced wall treatment. In summary, even though very little work has been done on characterising the effects of different modelling approaches when applied to swirling impinging jets, the diversity of works already done on other flow configurations also makes it hard to anticipate the sensitivity of specific models when applied to turbulent impinging jets.…”
Section: Introductionsupporting
confidence: 60%
“…(4) RNG K-ε turbulence model is applied for this investigation. Pulat et al [10] and Heck et al [11] reported that this model reflects the basic features of the jet flow. The conservation equations for the turbulent kinetic energy k and the dissipation rate ε are: Kinetic energy, k…”
Section: Governing Equations Gas Phasementioning
confidence: 90%
“…Gk represents the turbulence kinetic energy due to the mean velocity gradients. The constants of this model are recommended by Pulat et al[10]: Cµ = 0.09, Cε1 = 1.42, Cε2 = 1.68, = 1.393, = 4.38 and β= 0.012…”
mentioning
confidence: 99%
“…μt=ρCμk2ϵ In the present study, the RNG k‐ϵ turbulence model is applied by considering the studies of Pulat et al and Heck et al They found that this model is suitable to simulate the impinging jet flow in stagnation zones and wall jet regions adequately. The equations for turbulent kinetic energy k and dissipation rate ϵ are:…”
Section: Cfd Model and Simulationmentioning
confidence: 99%